2021
DOI: 10.3390/bioengineering8100145
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic Characterization of Parasagittal Bridging Veins and Implications for Traumatic Brain Injury: A Pilot Study

Abstract: Many previous studies on the mechanical properties of Parasagittal Bridging Veins (PSBVs) found that strain rate had a significant effect on some mechanical properties, but did not extensively study the viscoelastic effects, which are difficult to detect with uniaxial simple tensile tests. In this study, relaxation tests and tests under cyclic loading were performed, and it was found that PSBVs do indeed exhibit clear viscoelastic effects. In addition, a complete viscoelastic model for the PSBVs is proposed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The only widely used injury metric or risk index to assess the likelihood of ASDH is the RMDM [ 13 , 14 , 15 ]. However, the empirical data from Löwenhielm which were used to construct RMDM [ 13 , 17 ] are in question, as it appears that many authors have not found ultimate strain to decay noticeably with strain rate in the range [ 11 , 12 , 22 , 25 ]. Using recent data, it has been found that at low strain rate , , increases significantly [ 11 ] and from s no significant changes are detected [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The only widely used injury metric or risk index to assess the likelihood of ASDH is the RMDM [ 13 , 14 , 15 ]. However, the empirical data from Löwenhielm which were used to construct RMDM [ 13 , 17 ] are in question, as it appears that many authors have not found ultimate strain to decay noticeably with strain rate in the range [ 11 , 12 , 22 , 25 ]. Using recent data, it has been found that at low strain rate , , increases significantly [ 11 ] and from s no significant changes are detected [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of the empirical data used is that viscoelastic effects in CBVs have been insufficiently studied [ 25 ]. Moreover, failure data available correspond to loading curves in which the strain rate is approximately constant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations